BIOGEOCHEMICAL PROCESSES IN COASTAL AQUIFERS AND PERMEABLE SEDIMENTS - Shaw T.J. (My University, 2003)
Recent changes in our understanding of the mechanisms of chemical exchange and benthic ﬂux in coastal systems has led to a paradigm shift in our assessment of chemical inputs to the ocean (Moore, 1999; Boudreau et al., 2001). Studies have demonstrated that discharge from coastal aquifers, and ﬂow through permeable sediments, constitute major mechanisms for chemical exchange in coastal systems (Moore, 1996; Huettel et al., 1996; Shaw et al., 1998; Moore, 1999; Huettel and Rusch, 2000; Jahnke et al., 2000; Krest et al., 2000; Boudreau et al., 2001). The articles presented in this volume reﬂect discussions that were part of a conference titled “Subterranean Coastal Environments: Biogeochemical Processes, Fluxes and Impacts” held at the Hanse Institute for Advanced Study in Delmenhorst, Germany, in May of 2001. Within this special volume, methods for evaluating the physiochemical conditions and processes that lead to ﬂow in permeable systems are discussed as well as some of the consequences to chemical exchange in coastal ocean environments. A brief overview of each of these articles and their signiﬁcance to understanding permeable systems is presented below.